FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 7 – 11 BULAN DI WILAYAH KERJA PUSKESMAS MACCINI SAWAH MAKASSAR - Andi Sani Silwanah (Jurnal Mitrasehat, 2016)
Exclusive breastfeeding is breastfeed without additional liquids such as formula milk , orange juice, honey , tea water , white water and additional solid foods such as banana , papaya milk porridge , biscuits , rice porridge and teams . Based on secondary data obtained from Maccini Sawah PHC Makassar showed that the amount of coverage of exclusive breastfeeding in 2012 as much as 98.17 % , in 2013 as much as 76 % , and by 2014 as much as 78 %. The aim of this research is to know association between mother’s occupation, advertising, and aesthetics and exclusive breastfeeding on infants aged 7-11 months This was analytic observational with cross sectional design. Sample was infant aged 7-11 month who visited to Maccini Sawah PHC Makassar. The number of sample was 51 respondents. sampling technique was purposive sampling. data processing using SPSS and analyzed using chi square test and fisher exact test as alternative. This study showed that occupation (p=0,001), advertising (p=0,002) were associated to exclusive breatfeeding. Meanwhile, aesthetich has no relationship to esclusive breastfeeding on infant aged 7-11 month. There is not relationship between aesthetics and exclusive breastfeeding . While the mother's occupation and advertising were associated to exclusive breastfeeding . Suggestion for health providers Maccini Sawah Makassar to keep improving their role in providing information to mothers on exclusive breastfeeding.